Article NUTRITIONAL INTERVENTION IN ADOLESCENTS WITH AUTISM SPECTRUM DISORDER (ASD) AND FOOD SELECTION: A CASE STUDY - de Lima, Wanessa Vitória Soares; Paes, Andrea Karla da Silva Perciano; Filho, Valdenor Carvalho Maciel (Brazilian Journal of Implantology and Health Sciences, 2024)
This study aims to investigate nutritional intervention in adolescents with Autism Spectrum Disorder (ASD) and its relationship with food selectivity, through a case study. Food selectivity is a common characteristic in individuals with ASD, manifesting itself in the preference for foods with little variety, specific textures and colors, which can affect adequate nutritional intake and lead to nutritional deficiencies. The proposed nutritional intervention aims to improve the quality of the diet, promoting the inclusion of more varied and balanced foods, respecting the sensory and behavioral needs of adolescents. The adopted methodology involves the application of personalized strategies, such as the use of sensory and behavioral approaches, individualized nutritional monitoring and educational sessions for parents and guardians. The expected results include improved acceptance of varied foods, promotion of healthier eating habits and reduction of nutritional deficiencies associated with food selectivity. This study highlights the importance of a specialized nutritional approach for adolescents with ASD, contributing to the general well-being and healthy development of this population.